Securing the emperor, securitising the guns: the strangely delayed dissemination of Ottoman military technology in the late Ming empire - Noordam, Barend (Journal of the British Academy, 2021)
This article analyses the reasons behind the delayed appropriation and adoption of Ottoman harquebuses by the Ming army. Although these weapons had reached the empire by the mid-16th century, their existence was only acknowledged at the end of the century. Through the lens of securitisation, I will argue that this delay was a result of the context of Luso-Ottoman geopolitical rivalries in which these weapons were possibly leveraged as an incentive to form a Sino-Ottoman alliance against the Portuguese. I will argue that a civil bureaucracy averse to assertive activist rulership could have prevented the emperor from participating in the resulting military diplomacy. By comparing this event with a later Dutch East India Company embassy with similar geopolitical intentions, I will argue that the Ming civil officials achieved their goal by controlling the emperor's perception of Ottoman intentions. In terms of securitisation, this meant that the emperor himself was the main audience and his officials the securitising agents in matters of foreign relations.
Gesehen am 16.01.2026